Temporal Patterns and Variations in HIV/AIDS detection: Notifications in Brazil (2013-2022) - Marconato, José Victor; Genaro, Luis Eduardo; Valsecki Júnior , Aylton; Lopez Rosell , Fernanda (Brazilian Journal of Sexually Transmitted Diseases, 2024)
Introduction: Acquired Immunodeficiency Syndrome (AIDS) is the advanced stage of Human Immunodeficiency Virus (HIV) infection, compromising the immune system and rendering the body vulnerable to various opportunistic infections. Since the 1970s, AIDS has posed a global challenge, impacting Brazil since 1982. Despite advancements, the disease’s persistence necessitates comprehensive strategies and a deep understanding of transmission methods for effective management. Objective: This study aims to comprehend HIV/AIDS detection in Brazil (2013–2022). Analyzing temporal patterns, it guides future prevention and control strategies, emphasizing the need for effective approaches in the dynamic epidemic scenario. Methods: This cross-sectional study analyzes HIV case notifications in Brazil (2013-2022) utilizing data from the Unified Health System’s Department of Information and Informatics (DATASUS), covering macro-regions, Federative Units, and capitals. Detection rate data are sourced from the Notifiable Diseases Information System (Sinan), Mortality Information System (SIM), Laboratory Exams Control System (Siscel), and Medication Logistic Control System (Siclom), considering sociodemographic variables and exposure categories. The analysis aims to understand the dynamics of HIV/AIDS in the country. Results: Between 2013 and 2022, AIDS cases in Brazil predominantly affect men, with an increase after 2020. The HIV detection rate by region reveals significant variations, highlighting fluctuations in the North and South. Educational data suggest a reduction in cases, indicating the impact of preventive programs. The analysis by race/color shows a consistent decline in cases among whites, blacks, and browns, while yellows and indigenous populations exhibit variations. Conclusion: The conducted analysis highlights the complexity of AIDS dissemination in Brazil, underscoring the need for regionally adapted strategies. Variations by region, education levels, and race/color emphasize the importance of multifaceted approaches, continuous prevention programs, and addressing social inequalities.